The effect of muscle stretching exercises on the peripheral speed of the throwing arm and achievement in discus throw for people with disabilities, category F34. - Thaer Muzahim Kazim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Flexibility exercises (muscle stretching) are physical exercises that aim toimprove and develop some motor skills. Given the importance of musclestrength in the skill performance of discus throwing for people with disabilities,the longer the muscle, the greater the force it gives, which is directlyproportional to the distance achieved by the thrower. The ability of the muscle tostretch, which reaches half the length of the muscle, gives greater strength andspeed to the arms when performing. This comes through some exercises for thethrower's arm that contribute positively to this aspect. The aim of the study wasto identify the effect of muscle stretching exercises on the peripheral speed ofthe throwing arm and achievement in discus throwing for people withdisabilities in the F34 category sitting. The hypothesis of the research was thatthere were statistically significant differences between the pre- and post-tests inthe peripheral speed of the throwing arm and achievement in discus throwing forpeople with disabilities in the F34 category sitting, in favor of the post-test. Theresearcher used the experimental method using the single-group method, andmuscle stretching exercises were used for the throwing arm to increase its abilityto develop peripheral speed as well as achievement. The exercises continued for(6) weeks with (3) training units per week. After conducting the post-tests, theresearcher concluded: